Comparison of first-line and second-line use of fingolimod in relapsing MS: The open-label EARLIMS study. Issue 3 (September 2020) - Fernández, Oscar; Izquierdo, Guillermo; Aguera, Eduardo; Ramo, Cristina; Hernandez, Miguel; Silva, Diego; Walker, Rob; Butzkueven, Helmut; Wang, Chenyu; Barnett, Michael; ,
Background: Treatment of MS often begins with low-efficacy injectable disease-modifying therapy (iDMT). Objectives: To compare the effect of fingolimod 0.5 mg/day on clinical, MRI, patient-reported, and safety outcomes, in treatment-naïve and previously treated (≥1 iDMT) patients with early MS. Methods: EARLIMS was a multicentre, open-label, non-randomized, parallel-group phase 3 b/4 study in Australia and Spain. Patients with relapsing–remitting MS, Expanded Disability Status Scale (EDSS) score <4.0, and ≥1–5 years since diagnosis, received daily fingolimod for 48 weeks. The primary endpoint was annualized relapse rate (ARR). Results: Of 347 patients enrolled at 51 sites (treatment-naïve, 200 [57.6%]; previously treated, 147 [42.4%]), 320 completed the study (treatment-naïve, 184 [92.0%]; previously treated, 136 [92.5%]), but the study remained underpowered (planned enrolment, n = 432). Fingolimod reduced ARR to similar levels in both treatment-naïve (mean ARR [95% confidence interval], 0.21 [0.14, 0.29]) and previously treated groups (0.30 [0.20, 0.41]; p = 0.1668). There were no new safety signals. Conclusions: Fingolimod appeared equally effective as first- or second-line therapy in relapsing MS. There was a trend for better outcomes with fingolimod in treatment-naïve patients than in those previously treated with >1 iDMT.